Komodifikasi Dakwah dalam Industri Kosmetik: Analisis Iklan Wardah dari Perspektif Cultural Materialism - Wulansari, Retno Ayu Dwi; Prameswari, Lintang (UIN Sunan Ampel Surabaya, 2026)
This study aims to examine the commodification of da'wah in the halal cosmetics industry through the advertisement Wardah Ramadan Series Episode 3: Bersabar Jadi Berkah, published on YouTube in 2025. This study employs a qualitative approach using Multimodal Content Analysis (MCA) to examine the interaction of linguistic, visual, audio, and digital elements in constructing meaning. The analysis is framed by Raymond Williams' Cultural Materialism perspective to explain how the representation of da'wah in media is closely connected to economic interests and broader cultural structures. The findings reveal three major forms of commodification. First, da'wah is constructed as a moral value that reinforces brand identity through narratives emphasizing patience and family piety. Second, da'wah is represented as a visual aesthetic that shapes consumer identity through religious symbols, including the hijab, domestic settings, natural makeup, and soft color palettes that portray the image of the modern Muslim woman. Third, da'wah functions as digital capital, in which religious messages are strategically designed to generate measurable audience engagement through views, likes, comments, and shares. The study concludes that da'wah in the advertisement no longer operates solely within a neutral spiritual domain but has become embedded in cultural practices closely linked to economic interests in digital media.